Confidence Judgment and Test Scores: Basis for Proposed Confidence Enhancement - Eseo, Tristan M; Mangaoil, Armina B; Sedilla, Bettina M (EDUCARE, 2017)
ABSTRACT: One of the structured experiences of high school students is taking test. This experience is usually prepared as a regular academic activity in school. It aims to measure studentsâ achievement, which can be gleaned from their test score. How the students provide their impressions or predictive response before they see actual test material and after taking the test are implicit valuations. Thus, implicit valuations are the predictions that answer the question, âwhat will be their actual test score in mind?â. The study investigates the confidence judgment and test scores of graduating high school students by determining their differences, which are the bases for developing a program to enhance student confidence in test-taking. Its participants consist of five hundred seventy five (575) graduating students from San Pablo City National High School in the Province of Laguna, Philippines. The researchers used two instruments, which are the test prediction forms and teacher-made test. The findings showed that (1) there is a significant difference between the studentsâ pre-test prediction and post-test prediction; (2) there is a significant difference between the studentsâ pre-test prediction and actual test score; and (3) there is a significant difference between the studentsâ post-test prediction and actual test score. It is concluded that studentsâ are generally overconfident. Furthermore, it is recommended that there is a need to identify factors that affect studentsâ overconfidence. A module was proposed based on the findings of research.Â  KEY WORDS: Confidence Judgment; Test Scores; Test Prediction Forms; Teacher-Made Test; Confidence Enhancement.Â Â Â Â About the Authors: Tristan M. Eseo is a Special Education Teacher at the Paaralang Pag-ibig at Pag-asaÂ atÂ San Pablo City, Laguna, Philippines. Prof. Armina B. Mangaoil and Bettina M. Sedilla, Ph.D. are the Lecturers at theÂ Faculty of Behavioral and Social Sciences PNU (Philippine Normal University), Taft Avenue, Manila 1000, Philippines. For academic interests, the authors can be contacted via their e-mails at: tmseo77@firstasia.edu.ph, mangaoil.ab@pnu.edu.ph, and bettinasedilla@yahoo.comHow to cite this article? Eseo, Tristan M., Armina B. Mangaoil & Bettina M. Sedilla. (2017). âConfidence Judgment and Test Scores: Basis for Proposed Confidence Enhancementâ in EDUCARE: International Journal for Educational Studies, Vol.9(2), February, pp.121-128. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Chronicle of the article: Accepted (October 9, 2016); Revised (January 20, 2017); and Published (February 27, 2017).